Density, heat capacity and thermal conductivity of liquid egg products - Coimbra, JSR; Gabas, A. L.; Minim, L. A.; Rojas, EEG; Telis, VRN; Telis-Romero, J. (Elsevier B.V., 2006)
Density, heat capacity and thermal conductivity of liquid egg products, such as egg white, egg yolk, whole egg and various white and yolk blends, were determined as affected by temperature and water content ranging from 273 to 311 K and 51.8 to 88.2% (mass), respectively. Polynomial models fitted the experimental data very well, showing a linear relationship both for temperature and water content. (c) 2005 Published by Elsevier Ltd.